Endopulmonary Bronchoalveolar Lavage Cytogram in the Prediction of Infective Pulmonary Complications in Concomitant Injury - V. I. Kartavenko; L. K. Romanova; V. D. Kreimer; L. M, Svirskaya; A. L. Purundzhan; A. V. Mironov; L. F. Makarova; R. S. Bugrilova (Общая реаниматология)
The purpose of the study was to examine the time course of changes in the cellular composition of bronchoalveolar lavage (BAL) fluid to assess the possibilities of using the values of an endopulmonary cytogram (EPC) for the prediction of the development of infectious pulmonary complications and death in victims with severe concomitant injury. Sixty-three victims divided into 2 groups by the injury severity scale (ISS) (Beaker et al., 1974) were examined. For BAL sampling, a BF-XT40 endoscope (Olympus, Japan) was applied to bronchofibroscopy. To study BAL, the authors used the routine cyto-logical techniques and compared the latter’s results with those of EPC. The data were statistically processed, by employing the Statistica 6.0 programs; p Kozlov I. A., Poptsov V. N. Combined Therapy with Nitric Oxide and Surfactant-BL for Acute Respiratory Distress Syndrome After Operations Using Extracorporeal Circulation ….15 Abstract Выбрать Показать< /> The present study was undertaken to comparatively evaluate the efficacy of inhalational nitric oxide alone and in combination with surfactant-BL in the complex therapy for acute respiratory distress syndrome (ARDS) after surgery under extracorporeal circulation (EC). The study included 53 patients aged 21 to 76 years. It has revealed that in ARDS that complicates operations under EC, the use of surfactant-BL during therapy with inhalational nitric oxide enhances the latter’s effects on arterial oxygenation, accelerates the regression of pulmonary oxygenizing dysfunction, and reduces the duration of artificial ventilation and the length of stay in an intensive care unit.